2019
DOI: 10.1152/ajpendo.00386.2018
|View full text |Cite
|
Sign up to set email alerts
|

Chronic maternal cortisol excess during late gestation leads to metabolic alterations in the newborn heart

Abstract: Our laboratory has previously shown in an ovine model of pregnancy that abnormal elevations in maternal cortisol during late gestation lead to increased fetal cardiac arrhythmias and mortality during peripartum. Furthermore, transcriptomic analysis of the fetal heart suggested alterations in TCA cycle intermediates and lipid metabolites in animals exposed to excess cortisol in utero. Therefore, we utilized a sheep model of pregnancy to determine how chronic increases in maternal cortisol alter maternal and fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…There is some suggestion that triglyceride uptake and production is altered; increased expression of DGAT2, encoding an enzyme responsible for de novo synthesis of triglycerides, as well as LSR, encoding the protein responsible for uptake of triglycerides, was identified in the IVS. In our previous study of the newborn cardiac metabolome after maternal cortisol exposure, we found higher levels of di and triglycerides (Walejko et al, 2019). DGAT2 expression is linked to insulin resistance in muscle fibers (Levin et al, 2007).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…There is some suggestion that triglyceride uptake and production is altered; increased expression of DGAT2, encoding an enzyme responsible for de novo synthesis of triglycerides, as well as LSR, encoding the protein responsible for uptake of triglycerides, was identified in the IVS. In our previous study of the newborn cardiac metabolome after maternal cortisol exposure, we found higher levels of di and triglycerides (Walejko et al, 2019). DGAT2 expression is linked to insulin resistance in muscle fibers (Levin et al, 2007).…”
Section: Discussionmentioning
confidence: 74%
“…The peroxisomal pathway genes upregulated in the LV were associated with fatty acid production [PEX13, important in peroxisomal biogenesis (Maxwell et al, 2003); SLC27A, acyl CoA synthetase [Reviewed in Soupene and Kuypers (2008)]; and ACACB, catalyzing production of malonyl CoA, a negative regulator of acyl CoA uptake (Brownsey et al, 2006)]. In a study in our laboratory in newborn lambs born to ewes treated continuously with 1 mg/kg/d cortisol, cardiac levels of plasmenyl-phosphatidylcholines (plasmenyl-PC), plasmanyl-phosphatidylethanolamines (plasmanyl-PE), and cardiolipins (CL) were reduced whereas triglycerides and diglycerides were elevated (Walejko et al, 2019). Oxidized plasmalogen products are elevated in a porcine model of myocardial infarction, and are thought to play a role in protection against oxidative stress in the heart and in the brain (Schmid and Takahashi, 1968; Dudda et al, 1996; Brosche and Platt, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 11β-HSD2 is expressed in a number of tissues [75]. Then, a chronic stressful situation in our life may produce true diseases [76] and, during pregnancy, can produce metabolic alteration in newborn heart [77]. Cortisol binds to glucocorticoids receptors, which are expressed in adipose tissue [78].…”
Section: Cortisolmentioning
confidence: 99%
“…specific cellular process in this complex network requires both global and local knowledge, acquired by the integration of multidisciplinary approaches (1,2). Metabolomics approaches have been successful in accelerating the elucidation of complex metabolic and physiological states of an organism and help complement biochemical and genetic approaches that can require significant resources and time (1,(3)(4)(5)(6)(7). Metabolomics has the benefit of providing a snapshot of all metabolic changes in a system without requiring that these differences produce an observable (growth) phenotype.…”
mentioning
confidence: 99%